تأثير الضغط المحصور على المقاومية التكوينية (Comprehensive Journal of Science, 2025)
This study examines how confined pressure affects formation resistivity.Generally discovered experimentally or using the factor . Forming resistivity factorapproach based on experience, using core samples chosen from three different oil fields.Some of these tests took place in the Sirte Basin of Libya.Laboratories of the Libyan Petroleum Institute (LPI Tripoli-Libya); many empiricalCorrelation helped to evaluate how restricted pressure impacted creativity.Resistor factor The best correlation coefficients are found using the best fit curve to ascertain how confined grain pressure influences formation resistivity factor. (Times New
Keywords: resisitvity ,pressure confined , Archie equation .